Maximum Modulus of Polynomials (Analysis in Theory and Applications, 2017)
Let $$P(z)= \sum_{j=0}^{n}a_j z^j$$ be a polynomial of degree $n$ and let $M(P,r)=\underset{|z|=r}{\max} |P(z)|$. If $P(z) eq 0$ in $|z|
Keywords: Maximum modulus; growth of polynomial; derivative.